Date night (20th Century Fox Home Entertainment, 2006)
An ordinary couple is in the right place, on the wrong night. Phil and Claire Foster are a sensible, suburban husband and wife slogging through their daily lives and marriage. But a case of mistaken identity sets off an outrageous chain of events involving small-time thieves, big-city mobsters, corrupt cops and a crazed cabbie, as the Fosters' 'date night' turns into a wild ride they'll never forget!